(untitled) (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2025)
Nigerian novelists have always expressed their views on various issues that affect the nation, from the colonial through the postcolonial era to the contemporary times, in varied novelistic styles. Bildungsroman appears to be the favourite baby of most third generation African women novelists. It has become a tool for (re)-creating the image and dream of a woman and a society. It is the same with Akachi Adimora-Ezeigbo, the author of Trafficked. The novel (re)-assesses the place of Nigerian (African) woman in the contemporary modern Nigerian society. Deploying Sigmund Freud’s psychoanalysis, it is discovered that the novelist finds the novelistic tradition of Bildungsroman useful as a tool to explore and demand paradigm shift in the popular perception and treatment of women both in individual and larger social circles. The novelist’s vision is to ignite social, cultural, and economic revolution that is aimed at repositioning Nigerian women to be at par with their male counterparts. The developmental trajectory of Nneoma, the protagonist, justifies the novel as a Bildungsroman.